Comparing and combining methods that enhance liquid–gas mass transfer in a batch reactor: Ultrasonic degassing, aeration by gas bubbling, and liquid agitation - W. Ludwig Kuhn; Jean-Yves Hihn; Bjørn Winther Solemslie; Ole Gunnar Dahlhaug (Ultrasonics Sonochemistry)
The present study investigates methods to enhance liquid–gas mass transfer in total dissolved gas (TDG) supersaturated water. Using a two-part experimental setup, water is first supersaturated using air, followed by an evaluation of the influence of various operating parameters on the volumetric liquid–gas mass transfer coefficient, kLa, in a liquid batch reactor. The dependence of this coefficient on sonication parameters is significant because of high partial pressure gradients with TDG supersaturation. The tested methods to enhance degassing are: ultrasonic degassing, aeration by gas bubbling, and agitation through flow circulation. The influence of the acoustic frequency and power, the gas diffuser porosity and flow rate, and the flow direction and velocity within the reactor were the parameters investigated for the respective method. In addition, a combination of the different methods was conducted to evaluate promoting effects on the liquid–gas mass transfer. Applying high-power ultrasound resulted in the largest mass transfer enhancement overall, even though aeration and liquid agitation increase the mass transfer when compared to natural degassing. Only a combination of ultrasound and liquid agitation through countercurrent flow leads to a small further enhancement in the mass transfer. Combining aeration by gas bubbling and ultrasound hampers the sonication process, but yields higher kLa values compared to aeration alone. The results indicate that high-power ultrasound, in combination with selected parameters, presents a powerful approach for efficient degassing of TDG supersaturated water. In addition, practical insights for applications within other fields are provided.